EDUCATIONAL DISCOURSE OF CHILDREN’S (9–12 YEARS) SUMMER FREE-TIME IN THE CONTEXT OF PARENTS’, AS ADULTS, CONCEPTIONS - Juodaitytė, Audronė (Acta Paedagogica Vilnensia, 2007)
The article analyses social, educational discourse of children’s summer free-time, emphasising parents’, as adults, conceptions. The information received during the conversation-interview with parents is being defined. Texts’ content analysis is being carried out and parents’ conceptions, that enable to state about perception of educational significance of children’s free-time, are being distinguished. Qualitative research has disclosed that: child’s “difference” during summer free-time is not acceptable to parents, since it is interpreted through child’s role in school study. Therefore, children become “unfamiliar” for their parents, as they are more independent, easily act in home surrounding, seek for new experience, observe, experiment, and choose activities. Their difference discord with previous parents’ images, the basis of which is formed by understanding that children’s activities, are adults’ concern. Parents are not ready to understand a child as an individual, managing to choose free-time’s content and forms. Consequently, such free-time situations, when children act differently comparing with school study time are not acceptable to parents. Parents’ conceptions regarding child’s self-expression are simplex, their notional context usually is as follows: “me and my child”, not “me” and “child” or “both of us”. The conception children’s free-time is the time that children can dispose at their own discretion to satisfy various needs (cognitive, communicational, recreational, hedonistic, etc) is not acceptable to parents. Children’s free-time in summer means new troubles for parents. In order to avoid this, parents enroll children in activities such as housework, working in the garden, kitchen garden, etc, making them stay in the surrounding that parents can easily control. Parents are not satisfied especially with child’s contemporaries, since they think that child becomes uncontrolled and unattended. Free-time is child’s activities that parents are responsible for – such summer free-time conception is acceptable to parents.